2018
DOI: 10.1007/s11442-018-1506-9
|View full text |Cite
|
Sign up to set email alerts
|

Investigating long-term trends of climate change and their spatial variations caused by regional and local environments through data mining

Abstract: Climate change is a global phenomenon but is modified by regional and local environmental conditions. Moreover, climate change exhibits remarkable cyclical oscillations and disturbances, which often mask and distort the long-term trends of climate change we would like to identify. Inspired by recent advancements in data mining, we experimented with empirical mode decomposition (EMD) technique to extract long-term change trends from climate data. We applied GIS elevation model to construct 3D EMD trend surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 55 publications
(45 reference statements)
0
7
0
Order By: Relevance
“…This method is useful for establishing an overall temperature trend but is insufficient to examine microclimate changes in detail. Data from fixed stations are often not representative of large areas and do not reflect local temperature variations (Xie and Zhang 2016). These stations are usually located in the central areas of the city or at certain critical points.…”
Section: Traditional Methods For Determining Urban Heat Island Effectmentioning
confidence: 99%
“…This method is useful for establishing an overall temperature trend but is insufficient to examine microclimate changes in detail. Data from fixed stations are often not representative of large areas and do not reflect local temperature variations (Xie and Zhang 2016). These stations are usually located in the central areas of the city or at certain critical points.…”
Section: Traditional Methods For Determining Urban Heat Island Effectmentioning
confidence: 99%
“…In this study, we adopted the major vegetation types (10) identified in the 1:1,000,000 vegetation map of China as the LULC classes for our analyses (Table 1) [34]. In recent decades, researchers have studied IMAR with a focus on LULC classification [35], grassland degradation [36], ecosystem stability [37], long-term climate change trends [38], and net primary productivity [39]. In these studies, RS images from Landsat and MODIS were important data sources for both input and validation.…”
Section: Study Areamentioning
confidence: 99%
“…It plays an important role in the hydrological, glacial and ecological modeling (Jóhannesson et al, 1995;Petersen et al, 2013;Wang et al, 2016a), because the gridding surface air temperatures which are interpolated based on the SATLR can significantly affect the melting surface Sun et al, 2015). Moreover, it is an important parameter in the fields of regional downscaling and reconstruction of high-resolution surface air temperature due to the strong relationship between air temperature and altitude (Dodson and Marks, 1997;Marshall et al, 2007;Yang et al, 2007;, which has an impact on the detection and attribution of regional climate change (Wilby et al, 2002;Xie et al, 2018).…”
Section: Introductionmentioning
confidence: 99%